High on/off ratio photosensitive field effect transistors based on few layer SnS2. (15th July 2016) - Liu, Jianzhe; Xia, Congxin; Li, Honglai; Pan, Anlian
Abstract: 2D layered SnS2 nanosheets have attracted increasing research interest due to their highly anisotropic structural, electrical, optical, and mechanical properties. Here, through mechanical exfoliation, few-layer SnS2 was obtained from as-synthesized many-layered bulk SnS2 . Micro-characterization and Raman study demonstrate the hexagonal symmetry structure of the nanosheets so fabricated. The energy band structures of both SnS2 bulk and monolayer were investigated comparatively. A highly photosensitive field effect transistor based on the obtained few-layer SnS2 nanosheets was fabricated, which shows a high I photo / I dark ratio of 10 3, and keeps the responsivity and external quantum efficiency ( EQE ) at a realistic level of 8.5 A W −1 and 1.2 × 10 3 % respectively. This 2D structured high on/off ratio photosensitive field effect device may find promising potential applications in functional electronic/optoelectronic devices or systems.